Human Resource Optimization in Digital Marketing: Synergy of Technology and Creativity - Kustiyono Kustiyono; Abdul Aziz (International Forum of Researchers and Lecturers, 2024)
Optimizing human resources (HR) in digital marketing through the synergy between creativity and technology is an important strategy to create effective and innovative marketing campaigns in the digital era. Creativity plays a crucial role in producing engaging and relevant content, which is able to build an emotional connection with consumers as well as strengthen the brand identity. Meanwhile, technology allows for personalization, data-driven analysis, and efficiency in the implementation of marketing strategies. This study examines how the combination of human resource creativity and the use of digital technology can create a competitive advantage for companies. The results of the study show that companies that successfully integrate these two elements can increase consumer engagement, customer loyalty, as well as the effectiveness of marketing campaigns. From a conceptual perspective, this approach is changing the way companies view innovation and cross-functional collaboration within organizations, which in turn improves responsiveness and adaptability to market changes. The practical implications of this research are the importance of investing in the development of creative and skilled human resources in technology, to create a sustainable digital marketing strategy and be able to compete in an increasingly competitive global market.